Heat transfer study in the low temperature thermal energy storage material (multi-component material) between tubes array during melting - Sulaiman, Suditama; Megat Ahmad, Megat Mohamad Hamdan; Sulaiman, Shamsuddin; Adam, Normariah (Penerbit UTM, 2005)
This paper is to present a simple and efficient numerical technique for solving transient multidimensional heat transfer problem of melting processes and comparison to an experiment result. The proposed technique comprises an enthalpy-based method for solving the problems by a finite difference scheme, lump system behavior being assumed for each node. The multi-dimensional transient heat transfer characteristics in term of temperature distribution history, the temporal storage heat and moving rate of solid-liquid interface in a multi-component phases change material (PCM) heated by the tube array under inline and staggered arrangement that have been studied numerically. Finite difference scheme for both time and space variable has been applied to solve the governing differential equation for obtained algebraic equation in explicit forms. The results are presented and discussed in this paper.